Leaving Japan observations on the dysfunctional U.S.-Japan relationship - Millard, Mike 1947- (M.E. Sharpe, 2000)
Written by an American journalist living and working in Japan, this book helps the reader understand the enormous problems inherent in both U.S. attitudes towards Asia, and in Japan's way of looking at and dealing with the world. It uses a narrative flow of personal reflections and interviews with both informed Western observers and many Japanese to present its main theme: criticism of the long-term assumption that Asian countries will become more American as they reap the benefits of capitalism.